วิเคราะห์ร่างพระราชบัญญัติหลักประกันทางธุรกิจ พ.ศ. ... : ศึกษาเฉพาะกรณีการนำกิจการมาเป็นหลักประกัน - วรินทรา ชาครพิพัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The objective of this thesis is to analyse problems and difficulties of project given as security in accordance with the Draft Secured Transaction Act B E. ...... The conclusion of this study has proposed appropriate approaches in dealing with certain problems and difficulties. This should be benefit to all parties who would use their projects as securities. According to the study, the researcher found that there are some limitations in using project as security in accordance with the Draft Secured Transaction Act B.E. .... The requirement that debt to be given as security must be Baht 500 Million in minimum prohibits a number of enterprises from giving a project as security. Moreover, the provision that allows courts to have authority to enforce and sell the security is also a limitation as the court procedure would delay the overall process and judges may have inadequate skills on enforcement. The researcher therefore recommended that the Draft Secured Transaction Act B.E. ..... shall be amended. Firstly, the minimum amount of debt requirement shall not be limited. Secondly, in case of enforcement and sale, the administrators in charge shall be directly authorized and the courts shall only monitor the administrators in charge to ensure that they have duly performed their duties. Furthermore, the researcher recommended that a contract should be concluded in order to settle the rights and duties amongst chargor, chargee and other parties with regard to the use of credit, the parties’ right to sell and transfer secured assets, and the right of other parties in project s assets. Respectively, the proposed alternatives would prevent and correct any mistakes likely to occurred in practice.